(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
The intimate apparel market is changing towards the personalized consumption environment rapidly. On one hand, consumers' behaviour is more selective; On the other hand, brassiere design and development cycle are getting shorter and shorter. Mould head design is a key process in producing brassieres. A master cone which is the prototype of the mould head can be developed by a novel parametric method. The example-based method can easily make a new mould head style from several existing styles of master cones only by adjusting corresponding weights. Through the remeshing and registration algorithm, designer can characterize the outer surfaces of the mould head and scanned bra cups, aligning them each other at a point with same topology for assessing deviation. The results from this paper provide a scientific, practical and effective solution for intimate apparel manufacturers so that they can improve the development process of mould heads.